2016
DOI: 10.1177/0886260516658756
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Post-Decision Attitudes of Non-Reporting Sexual Violence Victims

Abstract: Although the physical and psychological consequences of sexual violence can be severe, many victims do not report the violence to the police force. The current study examined the characteristics and the post-decisional attitude of the non-reporting sexual violence victims. In total, 287 victims of sexual violence completed an anonymous online questionnaire that assessed characteristics of the violence, whether or not the crime was reported, reasons for not reporting, and aspects that would have convinced non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…The perceived seriousness of experiences played a substantial role in shaping participants’ reporting practices, a finding that is mirrored in previous research (see Ceelen et al., 2016; Fisher et al., 2003; Lievore, 2005; Spencer et al., 2017). The majority of participants indicated that they had rarely, if ever, reported incidents perceived as less ‘serious’ (though how ‘seriousness’ is defined is far from universal – see Fileborn, 2016).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The perceived seriousness of experiences played a substantial role in shaping participants’ reporting practices, a finding that is mirrored in previous research (see Ceelen et al., 2016; Fisher et al., 2003; Lievore, 2005; Spencer et al., 2017). The majority of participants indicated that they had rarely, if ever, reported incidents perceived as less ‘serious’ (though how ‘seriousness’ is defined is far from universal – see Fileborn, 2016).…”
Section: Resultssupporting
confidence: 70%
“…Understandings of sexual violence are often filtered through the lens of common rape myths and misconceptions: that ‘real rape’ or sexual violence is perpetrated by a stranger, with unambiguous lack of consent and the use of overt violence or force (Carbone-Lopez et al., 2016; Chen & Ullman, 2010). Survivors whose experiences of sexual violence align with narrow constructions of ‘real rape’ are more likely to report and be afforded ‘legitimate’ victim status (Carbone-Lopez et al., 2016; Ceelen, Dorn, Van Huis, & Reijnders, 2016; Fisher, Daigle, Cullen, & Turner, 2003; Lievore, 2005; Spencer, Stith, Durtschi, & Toews, 2017). Survivors may not report due to a belief that they were responsible, or because of feelings of shame, embarrassment and fear (Brubaker, 2009; Ceelen et al., 2016; Felson & Paré, 2005; Fisher et al., 2003; Lievore, 2005; Weiss, 2010).…”
Section: Reporting Sexual Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated that victims are less likely to report if they know the perpetrator or have otherwise had some form of relationship prior to the rape (Sable et al, 2006). Victims are also less likely to report if the rape was non-violent, if it happened in the victim's or the perpetrator's home (Abbey, 2011;Ceelen et al, 2019;Lovett & Horwath, 2009), if the age difference between themselves and the perpetrator is not great or if they themselves had consumed alcohol or drugs (Ceelen et al, 2019;Donde et al, 2018;Larcombe et al, 2016;Weiss & Dilks, 2016). Other social factors that may influence the propensity to report rape include the victim's faith in the police and the criminal justice system in general (Kaukinen, 2004), whether the victim thinks friends, family and others will believe them, and, more generally, how they think others might react (Donde et al, 2018;Jordan, 2001).…”
Section: Reportable Rapesmentioning
confidence: 99%
“…14 Ceelen also reported a similarly low reporting rate of 20% with shame, guilt and lack of evidence as some of the reasons behind their decision. 23 Many of these reasons may be shared by the non-reporting survivors in our study.…”
Section: Discussionmentioning
confidence: 90%